LITERASI GEOGRAFIS DAN EKONOMI GLOBAL DALAM PEMBELAJARAN IPS - Rachmat Panca Putera; Mira Arini; Fajar Rahmalia; Ines Kinanti Sutisna (Jurnal Dinamika Pendidikan Islam, 2025)
This study aims to analyze the learning process of Social Studies (IPS) in elementary schools from the perspective of geographic literacy and global economic literacy. The study employed a qualitative approach with a descriptive-analytical design. The research subjects were teachers and students of grade III and grade VI at SD Negeri 2 Jojog, East Lampung. Data were collected through non-participant classroom observation and documentation analysis. The findings indicate that Social Studies learning on geographic content (maps) in grade III has introduced basic geographic literacy; however, student engagement remains uneven due to limited instructional media and strategies. Meanwhile, Social Studies learning on economic content (exports and imports) in grade VI demonstrates higher student engagement as the material is presented contextually and connected to real-life economic phenomena. Overall, geographic literacy and global economic literacy have not yet been systematically integrated in Social Studies instruction. This study recommends the development of integrative and literacy-oriented Social Studies learning to strengthen students’ understanding of the relationship between geographic space and global economic dynamics from the elementary level.